Chemical constituents and biological activity of Vitex rotundifolia / Siti Khadijah Sulaiman - Sulaiman, Siti Khadijah (2019)
Vitex rotundifolia L. is a plant belonging to Lamiaceae family consists of 270 species including tree and shrubs. It has been described as a deciduous woody vine plant that grows horizontally in sand dunes, beaches and rocky shoreline. This plant is mainly distributed in the tropical and sub-tropical region and a few species found in the temperate region including China, Taiwan, South Japan, Malaysia, India, Sri Lanka, Mauritius, Australia, Pacific Island and Hawaii. The fruit of this plant has been traditionally used for headaches, colds, migraine, eye pain, night blindness, myalgia and neuralgia.